Couples invoking shringara rasa framed in panels - Temples of India Project Team (Jio Institute, 2024)
Couples invoking shringara rasa (associated with romance, love, and attractiveness between lovers) are framed in panels with pillars and tiered shikhara with gavaksha (horseshoe) motifs. Unlike other sections of the temple, the faces of these couples are not damaged and they are wearing heavy jewellery, elaborate headgear, and garments, indicating their royal lineage. The central male figure is seated in the lalitasana pose on a raised seat. The central female figure is seated on his left thigh, looking towards the man with her head turned. The man is admiring the beauty of the woman, placing his left hand on her coiffure and inspecting her face with his left hand (missing). Chauri dharini (fly whisk bearers) stand on either side of the couple, looking towards them. A small female figure features at the right bottom and is likely an attendant or servant.